PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING LEARNING TERHADAP HASIL BELAJAR KETRAMPILAN PASSING BAWAH PADA PERMAINAN BOLAVOLI - Adinanta, Pratama Johan (Bravo's : Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2013)
ABSTRACT: This study aimed to determin the effect of learning models Contextual Teaching Learning (CTL) against bounce pass skill learning outcomes volleyball in class VII of MTS Darun Najah Jatirejo Mojokerto academic year 2014/2015            This type of research is a quantitative research using experimental methods. The population inthis research that the whole class VII MTs Darun Najah Jatirejo Mojokerto. Through cluster random sampling technique derived class VII B with the number of 30 students as the sample. The instrument is used as a data collection that test skills. Analysis of the data using SPSS V. 17            In research using SPSS count test (paired sample t-Test) with significance level = 5% was obtained t hitung = 16.018 and t table = 1.699. The reception area is Ho if t hitung < 1.699 then Ho accpepted. While the analysis of the results obtained t hitung value greater than t table so Ho is rejected. And merease is 8.04%. It can be concluded happen influence model learning of Contextual Teaching Learning  to the learning outcomes of bounce pass skill the volleyball